편타손상에 기인한 급성두통환자의 한방치료에 대한 후향적 증례 연구 - 김석우; 진소리; 박무진; 김동우; 강경래; 김수연; 오승주; 김은송; 진동은; Kim, Seok-woo; Jin, So-ri; Park, Moo-jin; et al. (대한한방내과학회지, 2020)
Objectives: The aim of this study was to report improvement of acute headache incurred in a traffic accident in five patients who underwent inpatient treatment with Korean medicine. Methods: We collected data for traffic accident patients with acute headache who were admitted to the Ja-Seng Hospital of Korean Medicine from November 2019 to April 2020 and received combinational Korean medical treatment. All patients had numerical rating scale (NRS) values of 6 or greater. The patients were treated with acupuncture, pharmacopuncture, herbal medicine, and chuna treatment. We measured the validity of the treatment with the NRS, Headache Impact Test-6 (HIT-6), and Henry Ford Headache Disability Inventory (HDI) at admission and on the date of hospital discharge. Results: At the end of the treatment, all patients showed decreases in NRS, HDI, and HIT scores. Conclusions: The combination of Korean medicine at admission was effective in five patients with acute headache after a traffic accident. However, the number of subjects was insufficient and individual efficacy was not measured in this study. Therefore, further studies are needed on this topic.